The effectiveness of spirituality therapy on psychological distress and resilience of thalassemia patients - zahra Yoosefian; hassan ahadi; adis keraskian mojmanari (مجله علوم روانشناختی, 2020)
Background: The emergence of chronic physical diseases such as thalassemia causes psychological distress and decrease of resilience in the patients with thalassemia. The present study aims to prove if spirituality therapy can lead to the decrease in the psychological distress and improvement of resilience of the patients with thalassemia? Aims: Therefore, the present study was conducted to investigate the effectiveness of spirituality therapy on the psychological distress and resilience of the patients with thalassemia. Method: The present study was quasi-experimental with pretest, posttest, and control-group with a two-month follow-up design. The statistical population of the present study included the patients with thalassemia in the city of Shiraz in the fourth quarter of 2018. 30 patients with thalassemia were selected through non-random voluntary and purposive sampling method and randomly replaced into experimental and control groups (15 patients in the experimental and 15 in the control group). The experimental group received ten ninety-minute spirituality therapy intervention sessions during two-and-a-half months. The applied questionnaires in this study were psychological distress questionnaire (Kesler, et.al, 2003) and resilience questionnaire (Conner and Davidson, 2003). The data from the study were analyzed through ANOVA by mixed design. Results: The results showed that spirituality therapy significantly influences psychological distress and resilience in the patients with thalassemia (P˂0/001). That way this treatment can reduce psychological distress and improve patient resilience. Conclusions: The findings of the present study implied that spirituality therapy can be used as an efficient therapy to decrease the psychological distress and resilience of the patients with thalassemia via techniques such as self-awareness and self-communication, altruism, forgiving the self and others, appreciation and gratefulness.